Assessing the sensibility and utility of a short-form version of the HIV Disability Questionnaire in clinical practice settings in Canada, Ireland and the USA: a mixed methods study. Issue 9 (29th September 2022) - O'Brien, Kelly K; Solomon, Patricia; Carusone, Soo Chan; Erlandson, Kristine M; Bergin, Colm; Bayoumi, Ahmed M; Hanna, Steven E; Harding, Richard; Brown, Darren A; Vera, Jaime H; Boffito, Marta; Murray, Carolann; et al.
Abstract : Objectives: The Short-Form HIV Disability Questionnaire (SF-HDQ) was developed to measure the presence, severity and episodic nature of health challenges across six domains. Our aim was to assess the sensibility, utility and implementation of the SF-HDQ in clinical practice. Design: Mixed methods study design involving semistructured interviews and questionnaire administration. Participants: We recruited adults living with HIV and HIV clinicians in Canada, Ireland and the USA. Methods: We electronically administered the SF-HDQ followed by a Sensibility Questionnaire (face and content validity, ease of usage, format) and conducted semistructured interviews to explore the utility and implementation of the SF-HDQ in clinical practice. The threshold for sensibility was a median score of > 5/7 (adults living with HIV) and> 4/7 (HIV clinicians) for ≥80% of items. Qualitative interview data were analysed using directed content analysis. Results: Median sensibility scores were > 5 (adults living with HIV; n=29) and > 4 (HIV clinicians; n=16) for 18/19 (95%) items. Interview data indicated that the SF-HDQ represents the health-related challenges of living with HIV and other concurrent health conditions; captures the daily episodic nature of HIV; and is easy to use. Clinical utility included measuring health challenges and change over time, guiding referral to specialists and services, setting goals, facilitating communication and fostering a multidisciplinary approach to care. Considerations for implementation included flexible, person-centred approaches to administration, and communicating scores based on personal preferences. Conclusions: The SF-HDQ possesses sensibility and utility for use in clinical settings with adults living with HIV and HIV clinicians in three countries.